الأدوار الحديثة للتدقيق الداخلي على ضوء مستجدات الإطار المرجعي الدولي للممارسات المهنية - كشاط, منى; بالرقي, تيجاني (جامعة الوادي - University of Eloued, 2017)
The International Professional Practices Framework « IPPF » who prepared by the Institute of Internal Auditors IIA as an ideal model which includes the best required practices for internal audit professionners and promotes ethical culture in their practices. The IPPF is being a tool for measuring the internal auditors’ performance, as well as being to give this Internal Audit Profession « IAP » universality feature. In the light of IPPF developments, it has created a new roles for auditors represented on the assessing the adequacy of internal control, risk management and corporate governance processes as well as evaluation of there effectiveness and improvement of thes processes, with a set of international standards of the professional practice and practices advisories.
Modern Roles of Internal Audit in light of the New International Professional Practices Framework
مقال
Keywords: التدقيق الداخلي; الإطار المرجعي الدولي للممارسات المهنية; الرقابة الداخلية ; إدارة المخاطر; الحوكمة; :Internal audit, International Professional Practices Framework, internal control, risk management, governance